The creative and cultural tourism ecosystem: A conceptual model - Josefina Salvado; Ana Maria Ferreira; Jaime Serra; Noemi Marujo (Dos Algarves, 2020)
The cultural tourism ecosystem includes a strong creative dimension, to which is added a complex interconnectivity between stakeholders, resources and organizations, which extends across various spatial and sectorial scales. This article seeks to synthesize the cultural and creative tourism “state of the art” as a platform for the construction of a theoretical model guiding creative experience. Proposing a theoretical model, the researchers show a way for a better understanding of the complex creative system, without focusing on details but suggesting a global point of view. The aim is to understand the links between the ideas, determine the importance and relevance of arguments and use to approach the problems in a consistent way. The study is based on a diverse documental analysis and literature review, and aims to suggest a new “Creative Tourism Ecosystem model” which creates and delivers unique tourism experiences (endorsing co-creation of value), integrates responsible and collaborative approaches among all stakeholders (increasing coopetition network strategies) and is a sustainable catalyst for low-population density areas (reinforcing and safeguarding the cultural landscape). As a result, several benchmarks will be presented to illustrate best practices.